PERBAIKAN RUTE BUS TRANS JOGJA DENGAN MENGGUNAKAN ALGORITMA FLOYD-WARSHALL - Fenny Fitriani; Eka Sudilowati (Unisda Journal of Mathematics and Computer Science (UJMC), 2018)
Yogyakarta is one of the city with the traffic problems. This is caused by many newcomers, students and workers, from outside the region Yogyakarta which contribute by donate jam level. Trans Jogja Bus is one of public transportation that provided by the goverment Yogyakarta to reduce traffic congestion. Trans Jogja bus has on several route. In this research is done study on the track of Trans Jogja bus. In this researsch, we used floyd-warshall algorithms to determained the rute of Trans Jogja bus. The results obtained from this algorithm is the remain rute of Trans Jogja Bus still not steady.